(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In the twenty-first century, population ageing is a major demographic issue for India. Withgrowing technology and the Digital World, it is difficult for the elderly to keep up with the latesttechnology. Elders are distracted and isolated by today’s continuouslyincreasing digital literacy andexcessive movement toward using online payment. Their daily lives, shopping, and Paytm utility billsbecome more difficult, and they become estranged from the younger generation who are digitally savvy.Digital literacy gives many benefits to the elderly to improve their quality of life.